Growth Factor Identification Based on Speed and Duration of Centrifugation in Platelet Rich Plasma - Rahmadian, Rizki; Raymond, Benni; Meksiko, Riki (Rumah Sakit Umum Pusat (RSUP) Dr. M. Djamil, 2024)
Background: This study aims to determine the appropriate preparation of simple PRP protocol to yield the maximum growth factor concentration, specifically for PDGF and TGF-β1. Methods: Blood samples were collected from 5 healthy volunteers who signed informed consent for participation in the study. The samples then processed by single centrifugation at 4 four different speed (600, 800, 1000, and 1200 rpm) for 4 different centrifugation times ( 8, 10, 12, 14 minutes). The Platelet Derived Growth Factor (PDGF) and Transforming Growth Factor β1 (TGF- β1) concentrations were determined by enzyme-linked immunosorbent assay (ELISA). Blood routine test analysis were measured by hematology analyzer. Results: The 8 min with 600 rpm centrifugation protocol resulted in a slightly greater release of TGF-β1 (7,127 ng/mL) and PDGF (473,909 pg/mL). While the other samples resulted from 50,296 pg/mL (14 min with 1200 rpm) until 406.883 pg/mL (8 min with 800 rpm) of PDGF. The other results of TGF-β1 vary from 0,558 ng/mL (14 min with 1200 rpm) to 6,322 ng/mL (10 min with 600 rpm). Conclusion: The highest concentration of PDGF and TGF-β1 were obtained from centrifugation process at 600 rpm for 8 minutes. Meanwhile, the lowest concentration of PDGF and TGF-β1 were obtained from centrifugation process at 14 min with 1200 rpm.